2016
DOI: 10.1590/1414-431x20165344
|View full text |Cite
|
Sign up to set email alerts
|

Depression and diagnosis of neurocognitive impairment in HIV-positive patients

Abstract: Neurocognitive impairment (NCI) is frequently observed in patients infected with human immunodeficiency virus (HIV) and results from the compromise of subcortical brain structures by the virus. The manifestations of NCI range from asymptomatic impairment to dementia. In addition to cognitive impairment resulting from HIV infection, other factors such as depression are associated with the loss of cognitive functions. The aim of this study was to estimate the prevalence of NCI in HIV-positive patients in a city … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 28 publications
1
46
1
2
Order By: Relevance
“…The 16 included articles—2 cohort [ 44 , 45 ] and 14 cross-sectional studies [ [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ]—were published between 2002 and 2017. Table 1 shows the characteristics of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…The 16 included articles—2 cohort [ 44 , 45 ] and 14 cross-sectional studies [ [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ]—were published between 2002 and 2017. Table 1 shows the characteristics of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…Depression is a significant problem encountered by people living with HIV because of its association with severe immunodeficiency and disease progression 27 . In this study, depression was associated with poor neurocognitive performance, which supports previous findings in which depression had the greatest association with neurocognitive loss 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In the multivariate model, only depressive symptoms were associated with NCI [ 29 ]. Further, the studies from the CHARTER group (CNS HIV Antiretroviral Effects Research) and other groups have demonstrated an association between mental health conditions and NCI [ 9 , 31 , 49 , 50 ]. However, Cysique affirms that depression and anxiety do not affect NCI [ 30 ].…”
Section: Discussionmentioning
confidence: 99%